CHARACTERISTICS OF THE ECONOMY IN RAPIDLY DEVELOPING COUNTRIES - Kgudoykulov, DSc, professor Khurshid (PT ANTIS International Publisher, 2024)
This article covers the theoretical and scientific basis of the specific features of the economy of rapidly developing countries with the opinions of foreign scientists. In addition, the differences between developed countries and rapidly developing countries are compared in their specific characteristics, this comparison includes economic growth, economic development, and the country's economy. In addition, the article presents a list of rapidly developing countries based on the report of financial investment companies